Assessing the Effectiveness of Biotechinicalslopestabilization Methods in Landslide Proneareas - Michael Vladimir (Uganda Christian University, 2025)
This research was conducted in Kasika village with a main aim of assessing the effectiveness of the different biotechnical slope stabilization methods in landslide prone areas. The study was triggered by the increasing challenge of slope instability in the area which led to loss of lives and destruction of community infrastructure such as roads, the study aimed at coming up with sustainable and environmentally friendly measures of stabilizing the slopes in the area. The study was conducted basing on three objectives that is to evaluate the slope susceptibility of the slopes to landslides in the landslide prone areas , to determine the factor of safety of the slope before failure and to assess the effectiveness of the biotechnical slope stabilization techniques. The study used (Analytical Hierarchy Process)AHP to come up with the landslide susceptibility map and morgenstern price method of slices to determine the factor of safety of the slope before failure under saturated and normal soil conditions. The study found out that the endangered slope was unstable and prone to landslides and recommended the use of the biotechinical slope stabilization method of brush layering with bamboo live cuttings(Oldenia Alpina) to stabilize the slope.
Undergraduate